ANALISIS KUALITAS PELAYANAN DENGAN MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT PADA MODERN LAUNDRY CIREBON - Roby Sentosa; Laura Lahindah; Linda Gandajaya (Bina Ekonomi, 2021)
Service Quality has a close relationship with customer satisfaction. Service quality provides an encouragement to customers to establish strong ties with the company. Customer satisfaction is created if customer’s needs or expectation can be met through the quality of services provided. The good or bad quality of the service depends on the ability of the service providers to consistently meet customer’s needs or expectation. The research was conducted on a business unit that offered services in the case of per-kilogram clothes washing, namely Modern Laundry. As a business unit that has a mature age, Modern Laundry must be able to know and make services that are needed and demanded by its customers. To be able to do it, a method is needed in this study. The method used in this study is QFD (Quality Function Deployment). The QFD method provides technical requirements by meeting the customer's voice with the company's voice. With the use of this method, companies are able to find out what is the customer's needs and demand, what services must be maintained, improved and eliminated. This study tested the validity and reliability so that the data used in this study were valid and reliable. The results of this study are there are several characteristics of customer needs and desires that must be prioritized by Moden Laundry. Not only these characteristics in this study the technical characteristics that need to be prioritized also by Modern Laundry.